Verbal art and the expression of the inexpressible: making sense of sensory experience - Bendix,Regina F. (2021)
Abstract Sensory matters have crossed paths with cultural scholarship for more than two centuries and have, during the past two decades, received renewed attention in ethnological fields and various publishing ventures. The working of the senses in tandem with cognition facilitates the experience of pleasure and pain, fear and elation - but to what extent can (or should) this realm, situated between individual experience and social coding, be accessible to cultural research? The paper probes a number of examples and methodological issues in grasping experiences and sites of interaction where sensations are expressed in a culturally shared fashion and explores which areas of research may profit particularly from an expanded ethnographic sensibility.